Antiepileptic Drug Prescribing Patterns and Seizure Control Among Outpatients with Epilepsy at a Public Hospital in Indonesia - Muhammad Faqih; Zakky Cholisoh; Nirma Seftiyanti; Ambar Yunita Nugraheni; Rizki Nur Azmi (Fakultas Farmasi Universitas Andalas, 2025)
Background: Epilepsy affects nearly 50 million people globally, including approximately 700,000–1.4 million in Indonesia, with 70,000 new cases reported annually. Objective: This study aimed to determine antiepileptic drug (AED) prescribing patterns and to examine their association with seizure control outcomes in patients with epilepsy. Methods: A descriptive cross-sectional analysis was conducted using 185 outpatient prescriptions. Data on patient demographics, seizure frequency, and AED regimens were collected. Patterns of monotherapy and polytherapy were analyzed descriptively, and seizure control was compared using chi-square analysis. Results: Of the patients evaluated, 48.6% were male and 51.4% female. Monotherapy was prescribed in 51.4% of patients, predominantly valproic acid (VPA) and phenytoin (PHT). Polytherapy was used in 48.6% of patients, with the most common combinations being VPA + carbamazepine (CBZ) and PHT + VPA. Seizure-free control within six months was achieved in 34.6% of patients. A significant association was found between therapy regimen and seizure control (p = 0.040), with poor control more frequent in polytherapy (73.3%) than monotherapy (57.9%). Patients on polytherapy had twice the risk of poor seizure control (OR = 2.00; 95% CI: 1.08–3.72). Conclusion: Valproic acid remains the most prescribed AED for monotherapy, while phenytoin–valproic acid combinations are frequent in polytherapy. Polytherapy was associated with poorer seizure control, highlighting the importance of individualized AED selection and rational drug utilization in epilepsy management